Autonomous vision-based detection of non-stellar objects flying in formation with camera point of view. (1st January 2014) - Benn, M.; Jørgensen, J.L.
The μ-advanced stellar compass (μASC) is a camera system which autonomously can provide attitude information based on the visible stars. An extended functionality of the μASC, called the vision-based sensor (VBS), enables the camera system to render rendezvous and docking navigation information for a formation flying spacecraft. The VBS system facilitates different operation modes, enabling i.e. inertial line-of-sight (LoS) solutions for any spacecraft reflecting more light than an Mv7 star. This paper will focus on the LoS solutions of the VBS system, with a thorough analysis of inflight performance and future mission aspects. The captured data used for the analysis presented in this paper, includes centroids from the VBS camera head unit (CHU) dedicated for inertial LoS operation and from the two standard startracker CHUs. By combining the data from these three CHUs, a total of 300 hours of operation distributed over the entire year is included in the thorough data analysis and performance characterisation.